Contact-induced grammar formation: A model from a study on Hiberno-English - Shimada, Tamami (Frontiers in Communication, 2022)
This article examines how certain characteristic grammatical forms in Hiberno-English (HE) are the result of a dynamic process of language formation guided by language contact. A first language contact between Irish and English gives rise to the grammar formation of HE, and a second contact between HE and other varieties of English, presumably over the past 50 years or so, has pruned HE to fit the speakers' awareness toward the standard norm. Examinations of the expressions of tense/aspect and information structure in HE lead to suggestion of grammatical oppositions being inherited from Irish and the resilience of this inheritance in present-day HE. Taking three salient characteristics of HE, the be after perfect, the do be habitual, and the 'tis….. construction as windows to its underlying properties, the article surveys earlier forms in the rise of HE and describes some facets of contemporary HE. One of the central issues in the examination is Irish language traits and their realization in HE morphosyntax. The article concludes by proposing an integrated perspective across the characteristics and a model to capture the grammar formation of HE, which can be applied to find similarities and contrasts with other language contact phenomena.